Bipolar switching polarity reversal by electrolyte layer sequence in electrochemical metallization cells with dual-layer solid electrolytes - Soni, Rohit; Meuffels, Paul; Petraru, Adrian; Hansen, Mirko; Ziegler, Martin; Vavra, Ondrej; Kohlstedta, Hermann; Jeong, Doo Seok (ROYAL SOC CHEMISTRY, 2013)
Bipolar switching behaviours of electrochemical metallization (ECM) cells with dual-layer solid electrolytes (SiOx-Ge0.3Se0.7) were analyzed. Type 1 ECM cell, Pt (bottom electrode)/SiOx/Ge0.3Se0.7/Cu (top electrode), exhibited typical eightwise current-voltage (I-V) hysteresis of ECM cells whereas Type 2 ECM cell, Pt (bottom electrode)/Ge0.3Se0.7/SiOx/Cu(top electrode), showed counter-eightwise hysteresis. In addition, absolute off-switching voltage in Type 2 cell is lower than that in Type 1 cell while on-switching voltage in both cells is almost the same. An attempt to understand this electrolyte-stack-sequence-depending switching polarity reversal was made in terms of the ECM cell potential change upon the electrolyte stack sequence and the consequent change in Cu filament growth direction. Relevant experimental evidence for the hypothesis was obtained regarding the switching behaviours. Furthermore, given the switching polarity reversal, feasibility of serial complementary resistive switches was also demonstrated.
Keywords: COMPLEMENTARY RESISTIVE SWITCHES; REAL-TIME OBSERVATION; ATOMIC SWITCH; DYNAMIC GROWTH/DISSOLUTION; CONDUCTIVE FILAMENTS; WORK FUNCTION; MEMORY CELLS; NANOIONICS; PLASTICITY; SYNAPSES